Paramedic survival guide - DiPrima, Peter A. Jr (McGraw-Hill Medical, 2012)
"The book every paramedic needs to enhance their career and job performance Paramedic Survival Guide offers both novice and experienced paramedics a unique blend of case studies, testimonials, and advice from veterans to help them succeed on their jobs and advance their career. The book also offers advice on how to pick the correct EMT job, the recruitment and interview process, and various career paths and options open to paramedics. Valuable features include "Taking it to the Street" boxes detailing must-know on-the-job information"--Provided by publisher.